Internal and External Environment Analysis on The Performance of Provincial Office of Indonesian Food and Drug Authority in Manado - Monik Umi Sakinah; Satya Aditya Wibowo (Journal of International Conference Proceedings (JICP), 2021)
Small and medium-sized businesses (SMEs) contribute significantly to the national economy. In 2018, North Sulawesi had a total of 48.45 thousand SMEs. Indonesian Food and Drug Authority (BPOM) has supports and provides convenience, protection and empowerment for SMEs. In accordance with BPOM's second mission, which is to facilitate the acceleration of the development of the Food and Drug business by partnering with SMEs in order to build a productive and competitive economic structure for the nation's independence. The purpose of this study was to determine the influence of internal and external environment analysis on the performance of Provincial Office of Indonesian Food and Drug Authority in Manado (BBPOM in Manado) as a Technical Implementing Unit (UPT) of BPOM related to registration assistance services to processed food SMEs in North Sulawesi. The company's external and internal environment can affect the company's performance to gain and maintain a competitive advantage. The external environment analysis using PESTEL analysis and Porter’s Five Force analysis while the internal environment analysis using VRIO analysis and RBV analysis. The results showed that internal and external environment analysis could affect on the performance of BBPOM in Manado.